2021
DOI: 10.4049/jimmunol.2001373
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: EPHB2 Is a Coreceptor for Fungal Recognition and Phosphorylation of Syk in the Dectin-1 Signaling Pathway

Abstract: Invasive fungal infections have become a leading cause of death among immunocompromised patients, leading to around 1.5 million deaths per year globally. The molecular mechanisms by which hosts defend themselves against fungal infection remain largely unclear, which impedes the development of antifungal drugs and other treatment options. In this article, we show that the tyrosine kinase receptor EPH receptor B2 (EPHB2), together with dectin-1, recognizes β-glucan and activates downstream signaling pathways. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There are high levels of IL-1β and IL-18 in the liver of schistosome-infected mice, and in HSC cells with highly activated NLRP3 inflammasome ( Meng et al., 2016 ). Dendritic cell-associated C-type lectin-1 (Dectin-1) is a C-type lectin-like pattern receptor that recruits and phosphorylates spleen tyrosine kinase (Syk) ( Sun W. et al., 2021 ). Activation of NLRP3 in HSCs caused by schistosome infections depends on the Dectin-1/Syk signaling pathway ( Figure 2 ), while inhibition of NLRP3 inflammasome activation significantly reduces egg granulomas and liver fibrosis ( Lu et al., 2017 ).…”
Section: Nlrp3 Inflammasome and Tlr2/4 Signaling Pathwaymentioning
confidence: 99%
“…There are high levels of IL-1β and IL-18 in the liver of schistosome-infected mice, and in HSC cells with highly activated NLRP3 inflammasome ( Meng et al., 2016 ). Dendritic cell-associated C-type lectin-1 (Dectin-1) is a C-type lectin-like pattern receptor that recruits and phosphorylates spleen tyrosine kinase (Syk) ( Sun W. et al., 2021 ). Activation of NLRP3 in HSCs caused by schistosome infections depends on the Dectin-1/Syk signaling pathway ( Figure 2 ), while inhibition of NLRP3 inflammasome activation significantly reduces egg granulomas and liver fibrosis ( Lu et al., 2017 ).…”
Section: Nlrp3 Inflammasome and Tlr2/4 Signaling Pathwaymentioning
confidence: 99%
“…It has also been reported that Dectin-1 recruits RAC1 to produce ROS, which play an important role in the clearance of intracellular fungi [ 13 ]. In recent years, an increasing number of antifungal immune regulators have been identified, including PLC-γ2, PKC-δ, SHP-2, TAGAP, and EPHB2 [ 9 , 10 , 14 16 ]. In addition to the innate immune system, the adaptive immune system also plays an indispensable role in host defense against fungal infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive inflammation results in renal immunopathology during candidiasis suggesting that other mechanisms or RCDs fine-tune immunopathology and fungal control. Emerging data from various studies indicate an essential function of non-classical β-glucan recognition during fungal infections [33][34][35][36][37][38] . We recently found that EphA2 acts as a β-glucan receptor in the oral cavity that triggers the production of pro-inflammatory mediators via STAT3 and MAPK on oral epithelial cells, while EphA2 induces priming of neutrophil p47 phox to increase intracellular reactive oxygen species (ROS) production to enhance killing of opsonized C. albicans yeast 33,34 .…”
Section: Introductionmentioning
confidence: 99%